One-visit RCT of maxillary incisors with extensive inflammatory root resorption and periradicular lesions: A case report - Asgary, Saeed; Ahmadyar, Maryam (Iranian Endodontic Journal, 2011)
ABSTRACT: Inflammatory external root resorption (IERR) is a pathological phenomenon of microbial origin. This study reports a case of external apical inflammatory root resorption of maxillary incisors associated with periradicular lesions in a 22 year old female, which was successfully treated by one-visit root canal therapy (RCT). Radiographic investigation revealed periapical radiolucencies in the upper incisors associated with varying degrees of external inflammatory root resorption of teeth 12, 21 and 22. One-visit RCT of all involved teeth was carried out. Access cavities were permanently restored after 1 week. Clinical and radiographic examinations at 1 day, 1 week and 14 month follow-up demonstrated complete resolution of patient’s signs/symptoms. The incisors were fully functional, and complete bone healing of the apical radiolucencies had taken place. The treatment outcomes demonstrated that IERR associated with periradicular lesions can respond successfully to one-visit RCT when conducted with adequate disinfection and a satisfactory coronal seal. Hence, one-visit RCT may be a good alternative to multiple-visit RCT involving intra-canal medicaments.